In-plane behaviour and damage assessment of masonry infills with hollow clay bricks in RC frames. (1st August 2018) - De Risi, Maria Teresa; Del Gaudio, Carlo; Ricci, Paolo; Verderame, Gerardo Mario
Highlights: An extensive database of experimental tests on RC frames infilled with hollow clay-masonry infills is collected. The main related numerical models existing in literature are compared with the experimental results. A simple practice-oriented equivalent nonlinear strut is proposed to model infills. Displacement capacity thresholds are identified and correlated to the infill in-plane response. Drift-based fragility functions at given performance levels are proposed. Abstract: Reinforced Concrete (RC) buildings with clay masonry infills are a very common structural typology worldwide for civil, strategic or productive use. Damage to infills may cause danger for human lives and strongly affects economic losses, as shown during past earthquakes. Despite their role is crucial in terms of global and local response of RC buildings in the event of an earthquake, in current practice, infills are considered as partition elements without any structural function. The behaviour of infills under seismic actions has to be reliably characterized, starting from the analysis of their displacement capacity at different performance levels due to in-plane actions, and a proper complete numerical modelling, able to reproduce their influence on the global behaviour of RC frames under seismic actions. Some models have been already proposed in literature, but their reliability should be yet proved on the basis of an as wide as possible experimental database. Therefore, in this paper, a homogenous extensive database of experimental tests on RC frames infilled with hollow clay-masonry infills – typical of Italian and Mediterranean RC building stock – is collected and presented. The experimental responses of the infills under lateral loads are obtained and the main related numerical models existing in literature are investigated and compared with the experimental results. A new modelling proposal is carried out to obtain a simple practice-oriented force-displacement envelope to significantly reduce the errors in the prediction of the infill in-plane behaviour under lateral loads. The experimental evolutions of damage under increasing displacement demand are also analysed, and the displacement capacity at given performance levels are identified and correlated to the in-plane behaviour of the infill panels. The analysis of the damage evolution to the infills during the experimental tests finally allows the definition of drift-based fragility functions for these components, representing a key point for a more reliable estimation of losses due to earthquakes.